SPECT in Focal Epilepsies - Roderick Duncan (Behavioural Neurology)
Brain perfusion changes during seizures were first observed in the 1930s. Single Photon Emission Computed Tomography (SPECT) was developed in the 1970s, and tracers suitable for the imaging of regional cerebral perfusion (rCP) became available in the 1980s. The method was first used to study rCP in the interictal phase, and this showed areas of low perfusion in a proportion of cases, mainly in patients with temporal lobe epilepsies. However, the trapping paradigm of tracers such as hexamethyl propyleneamine oxime (HMPAO) provided a practicable method of studying changes in rCP during seizures, and a literature was established in the late 1980s and early 1990s showing a typical sequence of changes during and after seizures of mesial temporal lobe origin; the ictal phase was associated with large increases in perfusion throughout the temporal lobe, with first the lateral, then the mesial temporal lobe becoming hypoperfused in the postictal phase. Activation and inhibition of other structures, such as the basal ganglia and frontal cortex, were also seen. Studies of seizures originating elsewhere in the brain have shown a variety of patterns of change, according to the structures involved. These changes have been used practically to aid the process of localisation of the epileptogenic zone so that epilepsy surgery can be planned.